2022
DOI: 10.3390/ijerph191710479
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Individuals in Japan Who Regularly Manage Their Oral Health by Having a Family Dentist: A Nationwide Cross-Sectional Web-Based Survey

Abstract: Dental healthcare systems may differ between countries; however, having a family dentist is generally important for proper oral health management. This study aims to analyze the proportion of people in Japan who have a family dentist, and their characteristics. A nationwide web-based survey with 3556 participants (1708 men and 1848 women) showed that 45.6% of men and 54.1% of women had a family dentist (FD group). A multiple logistic regression analysis revealed that men in the FD group mostly belonged to olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…In addition, the non-RDC group responded with significantly lower WTP values for dental checkups than the RDC group. Several previous studies have shown that income limitations are a barrier to regular dental attendance [8][9][10][11], and the results of this study support these previous findings from the perspective of economic evaluation of dental checkups. Based on these findings, it can be implied that compared to the RDC group, there is a limitation to the maximum amount that can be paid for dental checkups within a wide age range in the non-RDC group and that this may be associated with economic background factors; hence, this suggests the need for policy interventions.…”
Section: Association Between Wtp Values For Dental Checkups and Indiv...supporting
confidence: 90%
See 3 more Smart Citations
“…In addition, the non-RDC group responded with significantly lower WTP values for dental checkups than the RDC group. Several previous studies have shown that income limitations are a barrier to regular dental attendance [8][9][10][11], and the results of this study support these previous findings from the perspective of economic evaluation of dental checkups. Based on these findings, it can be implied that compared to the RDC group, there is a limitation to the maximum amount that can be paid for dental checkups within a wide age range in the non-RDC group and that this may be associated with economic background factors; hence, this suggests the need for policy interventions.…”
Section: Association Between Wtp Values For Dental Checkups and Indiv...supporting
confidence: 90%
“…Moreover, the results of this study showed that men had higher WTP values for dental checkups than women. Previous studies have shown that women are more likely to have an increased awareness of oral health than men [11,36]. However, according to a report by Japan's Ministry of Health, Labour and Welfare, the income of working men is about 2.1 times that of working women [31], and the reason for this is reportedly due to the differences in employment positions and length of service between men and women [37].…”
Section: Association Between Wtp Values For Dental Checkups and Indiv...mentioning
confidence: 99%
See 2 more Smart Citations
“…42 Additionally, an investigation of Japanese subjects revealed that having a family dentist was associated with socioeconomic status. 43 Our present findings may thus have been affected by selection bias, and their generalisability is therefore limited. Notably, however, the Specific Health Checkup introduced a new questionnaire item in 2018 about chewing ability.…”
Section: Discussionmentioning
confidence: 73%